Bahasa Inggris Pengaruh popularitas merek, persepsi kualitas, harga, dan kebutuhan pada niat pembelian produk iPhone di Purwokerto - Rizaldi, Herna (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
This study is a survey research that aims to determine and analyze the effect of brand popularity, perceived quality, price, and need on purchase intentions on iPhone products at Purwokerto city. The sample size in this study amounted to 120 using purposive sampling technique. Based on the results of data processing, it is known that brand popularity has no significant and negative effect on purchase intention. Price has a significant and negative effect on purchase intention. Perceived quality and need have a significant and positive effect on purchase intention. The findings in this study are that popularity is not always a consumer factor in generating purchase intentions, while the factor that has the greatest influence on purchase intentions is need.